2020
DOI: 10.3233/mnm-190363
|View full text |Cite
|
Sign up to set email alerts
|

Food literacy can described adequate? Optimizing cut-off scores for the short food literacy questionnaire (SFLQ)

Abstract: BACKGROUND: Preventing obesity and non-communicable disease is possible by making the right eating habits from early ages, therefore increasing food literacy level might be enforced in the preventive programs. OBJECTIVE:The objective of this study is to measure university students' food literacy level using "A short food literacy questionnaire (SFLQ) for adults" and determining cut-off point compared with health literacy. METHODS: Questionnaire was about Newest Vital Sign (NVS) test, Turkey Health Literacy SCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The identified studies used various types of health literacy related to the following health topics: general health31 32 34 35 42–67; nutrition68–82; non-communicable diseases (NCDs)36 63; HIV83 84; e-health39 85–91; media92; physical health93 94; oral health38 95; medical96; disability67 97 98; mental health37 40 41 99–108; suicide109 110; and depression 33 111. These studies used 36 scales to measure health literacy, and these scales can be grouped into three categories: newly developed scales66 77 82 86 93 98; newly adapted and translated scales33 40 41 43 54 55 64 69 83 96 100 111; and previously adapted and translated scales 34 35 38 39 44–46 49 51–53 56–59 62 65 67 68 71–73 76 78–80 85 87–89 91 95 97 103 104 107–110 112 113…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The identified studies used various types of health literacy related to the following health topics: general health31 32 34 35 42–67; nutrition68–82; non-communicable diseases (NCDs)36 63; HIV83 84; e-health39 85–91; media92; physical health93 94; oral health38 95; medical96; disability67 97 98; mental health37 40 41 99–108; suicide109 110; and depression 33 111. These studies used 36 scales to measure health literacy, and these scales can be grouped into three categories: newly developed scales66 77 82 86 93 98; newly adapted and translated scales33 40 41 43 54 55 64 69 83 96 100 111; and previously adapted and translated scales 34 35 38 39 44–46 49 51–53 56–59 62 65 67 68 71–73 76 78–80 85 87–89 91 95 97 103 104 107–110 112 113…”
Section: Resultsmentioning
confidence: 99%
“…General and nutrition-related health literacy were the most common health literacy themes addressed. In Turkey, 12 studies reported problematic or inadequate levels of health literacy among secondary school, high school and university students 45–47 49 53 54 57 63 70 77 79 109. Out of the eight studies conducted in Iran,35 36 46 64 68 70 73 80 one study reported that most high school students had adequate health literacy36 while five reported the opposite 35 46 64 70 73.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found a positive moderate correlation between the FL score based on SFLQ and the HL score calculated on the Turkey Health Literacy Scale-32 (TSOY-32) among the sample of adult respondents. The next study in a group of university students from Turkey revealed that the SFLQ score is significantly positively associated with general health perception and the habit of reading food labels [ 22 ]. The Italian version of the SFLQ was used by Trieste et al in the study conducted among Italian consumers [ 23 ].…”
Section: Introductionmentioning
confidence: 99%